He ahi kā, he poka rānei : to keep the fire burning or to extinguish the flame : a thesis presented in partial fulfilment of the requirements for the degree of Masters degree in Education at Te Kupenga o Te Mātauranga, Massey University College of Education, Palmerston North - Kenrick, Pani (Massey University, 2008)
He Ahi Ka, He Pōka Rānei- examines the provision of support offered to beginning teacher graduates of a total immersion Māori pre-service programme. Based on a Qualitative Māori centred approach, the study focuses on the ways in which the induction process, self-efficacy and professional development programmes within various classrooms and educational settings contribute to supporting the beginning teachers in this study. Issues related to access and participation in such support programmes and the contributions of key personnel to the provision of beginning teacher support are also explored. Through researching beginning teacher's, information gathered and analysed could be used when preparing and planning for professional development programmes to support beginning teachers from total immersion pre-service teaching programmes.
Keywords: Kura kaupapa Maōri; Mentoring; Education